Citrobacter rodentium is an unstable pathogen showing evidence of significant genomic flux. - Nicola K Petty; Theresa Feltwell; Derek Pickard; Simon Clare; Ana L Toribio; Maria Fookes; Kevin Roberts; Rita Monson; Satheesh Nair; Robert A Kingsley; Richard Bulgin; Siouxsie Wiles; et al. (PLoS Pathogens)
Citrobacter rodentium is a natural mouse pathogen that causes attaching and effacing (A/E) lesions. It shares a common virulence strategy with the clinically significant human A/E pathogens enteropathogenic E. coli (EPEC) and enterohaemorrhagic E. coli (EHEC) and is widely used to model this route of pathogenesis. We previously reported the complete genome sequence of C. rodentium ICC168, where we found that the genome displayed many characteristics of a newly evolved pathogen. In this study, through PFGE, sequencing of isolates showing variation, whole genome transcriptome analysis and examination of the mobile genetic elements, we found that, consistent with our previous hypothesis, the genome of C. rodentium is unstable as a result of repeat-mediated, large-scale genome recombination and because of active transposition of mobile genetic elements such as the prophages. We sequenced an additional C. rodentium strain, EX-33, to reveal that the reference strain ICC168 is representative of the species and that most of the inactivating mutations were common to both isolates and likely to have occurred early on in the evolution of this pathogen. We draw parallels with the evolution of other bacterial pathogens and conclude that C. rodentium is a recently evolved pathogen that may have emerged alongside the development of inbred mice as a model for human disease.